The evaluation of disc brake squeal propensity through a fully coupled transient thermomechanical model - Hassan, Muhammad Zahir; Brooks , P.C.; Barton, D.C. (SAGE Publications Ltd, 2013)
This paper presents a fully coupled transient thermomechanical analysis of a disc brake that takes into account the so-called ‘rotating-heat-source’ effect. Results from this are used to inform the time-based extraction of system eigenvalues that permit quantification of the squeal propensity of the brake. The model performance is validated against a series of dynamometer tests, based upon the SAE J2521 drag brake test schedule, in which the ability of the model to predict the fugitive nature of the squeal problem is confirmed. Finally, a parametric study is also presented that shows how the technique can be used to desensitise the squeal propensity to both material and geometric design changes.